Multiple intracerebral hematomas during SEEG recording and intradural hemorrhage after spinal tap: A case report prompting more research on collagen IV gene mutation and oral nicotine consumption as risk factors - Markus Leitinger; Serena Broggi; Mathias Spendel; Gudrun Kalss; Ivan Petrović; Herbert Krainz; Fabio Rossini; Julia Höfler; Andreea Toma; Giorgi Kuchukhidze; Matthias Mauritz; Kai‐Nicolas Poppert; et al. (Epilepsia Open, 2025)
Abstract Intracerebral hemorrhages (ICH) during implantation of stereo‐EEG electrodes are rare. The impact of tobacco‐free nicotine consumption on periprocedural bleeding is uncertain. We present a 20+ year‐old man with drug‐resistant epilepsy who underwent stereo‐EEG with 17 depth electrodes. Within a few days after insertion, the patient developed multiple ICHs in the electrode trajectories and an intradural hemorrhage after a diagnostic spinal tap. We performed the investigation of the clotting system and whole‐exome sequencing (WES). WES identified a heterozygous mutation c.4698G>T, p.(Trp1566Cys) in COL4A2 (NM_001846.4) encoding a collagen type‐IV alpha‐2 chain inherited from his seemingly healthy mother. As COL4A2 mutations had been identified in four adult patients with ICH we postulated that the identified variant presents a potential risk factor. Notably, mutations encoding other collagens have been linked to cerebral hemorrhages (COL4A1) and increased propensity to trigger ICH upon smoking (COL1A2). Our patient consumed at least 24 oral nicotine pouches (containing 11 mg nicotine each) per day. We consider the patient's COL4A2 mutation in combination with his substantial nicotine consumption as likely predisposition to multiple ICHs precipitated by stereo‐EEG. Patients with nicotine consumption and any collagen mutation may have a substantially higher risk for hemorrhagic complications in SEEG and other neurosurgical procedures. Plain Language Summary A young man with drug‐resistant epilepsy experienced multiple intracerebral hemorrhages after implantation of SEEG electrodes for presurgical evaluation and concomitantly a intradural hemorrhage after a lumbar spinal tap. A collagen IV mutation of unclear significance and heavy use of oral nicotine pouches were the only potential risk factors identified. As collagen mutations were previously described risk factors and smoking in particular worsens the bleeding risk in collagen mutations, further research is warranted to prevent hemorrhages in neurosurgical procedures. Nicotine consumption in any form is a preventable risk factor.